The Social Acculturation of The Abhekalaghi Tradition in Tempurejo from The Perspective of Islamic Law and Constitution No. 16 Of 2019 - Tamam, Badrut; Ramadhani, Meka Dina; Nawawi, Nawawi; Vais, Vais; Sofiana, Ririn; Rofiqoh A, Farah; Wicaksono, Syafril (Fenomena, 2023)
The Abhekalaghi tradition in Tempurejo is the social acculturation of the people there as a tradition that has been carried out from generation to generation in matchmaking of their children and marrying them off, but in its current developments, is this tradition still relevant in the perspective of Islamic law and Marriage Law No. 16 The year 2019 has provided a change in the implementation of marriage by giving a new norm in the form of limiting the age of marriage which makes this tradition still following the times and applicable legal provisions. Then the question arises: What is the background of the social acculturation of the Abhekalaghi tradition in carrying out marriages in the Tempurejo community, Jember. And how the implementation of this tradition is the perspective of Islamic law and Law No. 16 of 2019. The method used in this research is empirical juridical, a descriptive qualitative or field study using a sociology of law and legislation approach—data generated through direct interviews with the Tempurejo community for research sites. So, the results of research on the acculturation of the Abhekalaghi tradition in the Tempurejo community can be concluded that the background to this tradition is due to several factors such as economic factors, educational factors, local customs factors, parental factors, and social factors. Based on the view of Islamic law, the Abhekalaghi tradition is not prohibited because the 'Urf in this custom is more directed to 'Urf Hasan, which may be carried out following Islamic law that applies to that society. Then, we review Law No. 16 of 2019 regarding changes to Law No. 1 of 1974 concerning marriage, so we can see that many early marriages are being implemented because they are not following these regulations, which has led to an increase in dispensation for marriage in this society.